Social Design and Neocolonialism - Janzer, Cinnamon L.; Weinstein, Lauren S. (Design and Culture, 2014)
This article examines the current field of social design: its claims, practices, and methodologies. Findings discovered through qualitative research illuminate the current application of social design practices and offer critique around their use in the social sphere. This articl e argues that designers must be sensitive to a variety of complex soci al and cultural cues and structures or they risk contributing to, or p racticing, design neocolonialism. The article offers two key theoretic al suggestions to further the emerging field's progress. First, social design must shift its focus from one that is human-centered to one th at is situation-centered. Second, it is imperative that social design develops a shared framework for understanding, executing, and evaluati ng its initiatives and interventions. Additionally, this article intro duces a matrix to serve as an early iteration of a shared framework.
Keywords: Design Methodology; Design Thinking; Framework; Human-centered design; IMPORTANT; social design